Cybercrime and Threats to the Electoral System - Ni Komang Triana Andini; Ni Made Ayu Nadia Putri Damayanti; Ni Kadek Wintan Purnama Sari; Egidius Fkun; Moh. Erkamim (Catuspata, 2023)
Cyberattacks have emerged as a growing threat in the context of elections worldwide, posing significant risks to the integrity, security, and trustworthiness of electoral systems in today's digital age where information technology plays a pivotal role. Drawing from documented cyberattack cases and security reports from government agencies and related organizations during elections, common attack types such as Denial-of-Service (DoS), Phishing, and Malware have been identified. Cybersecurity systems and data sovereignty form the bedrock of personal data protection. As technology advances, data has become a highly valuable commodity, and a nation's data sovereignty intersects with the private sector on a global scale in political and economic terms. The state's primary responsibility lies in crafting regulations for data protection and cybersecurity, ensuring citizens' rights to personal data protection, which necessitates enhancing their capacity and capabilities. Therefore, this qualitative research delves into the imperative of developing citizens' capacity and capabilities in building cybersecurity and data sovereignty, with a particular focus on safeguarding personal data in the Indonesian context, as books and journal articles serve as valuable sources for data collection. Bolstering citizens' capacity and capabilities is essential for preserving their personal data in the digital realm.